Assessment of shell theories for cross-ply and angle-ply laminated cylindrical shells under thermo-mechanical loads - Rahman, Muhammad; Alsubari, Saleh; Syed Mohamed Ali, Jaffar; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (2021)
In this work, assessment of 2D shell theories and a new 13 term higher order shear deformation theory (HSDT13) is presented for simply supported anisotropic cylindrical shells under mechanical and thermal load. Equilibrium equations are derived through principle of virtual displacement and Navier type analytical solution are obtained for both angle-ply and cross-ply cylindrical shells for the case of generalized plane strain deformations in the axial direction. The in plane-displacement discontinuity is taken care by the use of Murakami zig-zag function in the new higher order shear deformation theory. Results are presented for both mechanical and thermal loading for various layups and they are validated against thermoelasticity solution.